2019
DOI: 10.7570/jomes.2019.28.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Body Mass Index, Body Image, and Depression in Korean Adults: Korea National Health and Nutrition Examination Survey 2014 and 2016

Abstract: Background This study extends the findings of our previous examination of the relationship between obesity and depression in Korean adults. Here, we further investigate the relationships among body image perception, weight control method, and depression based on data from the Korea National Health and Nutrition Examination Survey in 2014 and 2016. Methods In total, we analyzed 11,782 participants. We classified them into four groups according to body mass index (BMI): u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
(20 reference statements)
5
15
0
Order By: Relevance
“…Our finding of the inverse association between obesity and depression among Chinese rural population was consistent with those reported in Korea, Taiwan and Japan [ 19 , 29 31 ]. In addition, some previous studies in China have also observed an inverse association between obesity and depression [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of the inverse association between obesity and depression among Chinese rural population was consistent with those reported in Korea, Taiwan and Japan [ 19 , 29 31 ]. In addition, some previous studies in China have also observed an inverse association between obesity and depression [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, increasing evidence has been presented showing that these diseases are interrelated. [8][9][10][11] In order to prevent obesity in Turkey, 81 obesity centers have been opened in 34 provinces. The aim of these centers is to help patients reach their ideal weight, prevent patients from being di-…”
Section: Introductionmentioning
confidence: 99%
“…The underweight group was found to have a low alcohol consumption rate, which might be due to stop drinking with the consequences of harmful health problems, and also had the highest level of stress awareness. The authors2 noticed that these results appear to reflect the fact that younger participants, especially women, are more easily affected by the social ideology preference for a thin, slim figure.…”
mentioning
confidence: 98%
“…Studies of depressive outcomes account for much of the growing literature on the relation between obesity and psychological morbidity 1. Hong and Hong2 investigated the association between body mass index (BMI) and depression, in addition to the relationships between body image perception, weight control behaviors and depression. They found that the risk of depression was higher in the underweight group than in the obese group.…”
mentioning
confidence: 99%
See 1 more Smart Citation